Pathogen growth and virulence dynamics drive the host evolution against coinfections - Srijan Seal; Dipendra Nath Basu; Kripanjali Ghosh; Aryan Ramachandran; Rintu Kutum; Triveni Shelke; Ishaan Gupta; Imroze Khan (Proceedings of the National Academy of Sciences, 2025)
The occurrence of coinfections, where hosts are simultaneously infected by multiple pathogens, is widespread in nature and has significant negative impacts on global health. In humans, over one-sixth of the world’s population is affected by coinfections, contributing to several diseases. However, despite the broad ecological relevance and impact on global health, most biomedical research has focused on understanding interactions between a single host and a single pathogen. The extent to which coinfections could impact host adaptation and immune system evolution, particularly in comparison to infections by single pathogens, thus remains largely unknown. Also, what roles do individual pathogen species play in this evolutionary process? To address these questions, in this study, we combined theoretical modeling and experimental validation in a model insect Tribolium castaneum evolving against two coinfecting bacterial pathogens with contrasting growth (e.g., fast- vs slow-growing) and virulence (fast- vs slow-killing) dynamics. Our findings show that fast-growing pathogens causing rapid mortality surges (i.e., fast-acting) can effectively limit the host’s adaptive success against coinfections. While hosts rapidly evolved better survival against slow-growing bacteria causing long-lasting infections, adaptation against coinfections was significantly delayed and resembled the slow rate of adaptation against fast-acting pathogens. Finally, RNAseq analyses revealed that the observed delay in adaptation was associated with the limited scopes for suitable immune modulations against fast-acting pathogens. They might also be costly and pleiotropic (e.g., phenoloxidase activity), posing challenges for further immunomodulation and slowing adaptation. Our study thus highlights how individual pathogens’ growth and virulence dynamics critically regulate adaptive responses against coinfections.